HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PEMBERIAN ASI EKSKLUSIF PADA IBU MENYUSUI DI PUSKESMAS BAHU KOTA MANADO - Wowor, Mariane; Laoh, Joice M.; Pangemanan, Damajanty H.C. (JURNAL KEPERAWATAN)
Abstract: Exclusive breastfeeding is breastfeeding without supplemental food and other beverages such as infant formula, juice, honey, water, tea, water. According to data taken in 2010 from the Health Research Association, the percentage of infants who are breastfed exclusively in Indonesia is 15.3%. This is because of the mother's lack of knowledge, lack of support from environmental and health practitioners, provision of food and drinks too early, and widespread promotion of infant formulas. This study was conducted to determine the relationship of knowledge and attitudes to breastfeeding mothers at comunity health center Bahu in 2013. Design research is an analytical survey of the cross-sectional design, the population of lactating mothers of infants aged 0-6 months who came to visit at the health center shoulder. The study sample 38 respondents obtained using purposive sampling technique.The research instrument used a questionnaire that consists of 3 parts: knowledge, attitude and observation sheet breastfeeding. The results showed 33 respondents (86.8%) had good knowledge. Having performed statistical tests using Spearman's rho test showed p = 0.000 < 0,05 so, there is showed relationship knowledge of the breastfeeding. For attitudes to breastfeeding relationship is obtained with a value of p = 0.036 < 0,05 indicates that there is a relationship between attitudes to breastfeeding. Suggestions for health care workers, should further improve counseling and an introduction to the benefits of exclusive breastfeeding because it will help provide encouragement and motivation in breastfeeding mothers for provide care to their children. Keywords: knowledge, attitude, Exclusive Breastfeeding Abstrak : ASI Eksklusif adalah pemberian ASI tanpa tambahan makanan dan minuman lain baik susu formula, jeruk, madu, air, teh, air putih. Menururt data pada tahun 2010 yang diambil dari Riset Kesehatan Dasar, persentase bayi yang mendapat ASI ekslusif di Indonesia adalah 15,3%. Kendala ini disebabkan karena kurangnya pengetahuan ibu, kurangnya dukungan dari lingkungan dan praktisi kesehatan, pemberian makanan dan minuman terlalu dini, serta maraknya promosi susu formula untuk bayi. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan dan sikap dengan pemberian ASI pada ibu menyusui di Puskesmas Bahu tahun 2013. Desain penelitian yaitu survei analitik dengan rancangan cross sectional, populasi yaitu ibu menyusui bayi usia 0-6 bulan yang datang berkunjung di Puskesmas Bahu. Sampel penelitian ini 38 responden yang didapat dengan menggunakan teknik purposive sampling. Instrumen penelitian yang digunakan berupa kuesioner yang terdiri dari 3 bagian yaitu pengetahuan, sikap dan lembar observasi pemberian ASI. Hasil penelitian menunjukan 33 responden (86,8%) memiliki pengetahuan baik. Setelah dilakukan uji statistik dengan menggunakan uji spearman’s rho didapatkan hasil p = 0,000 < 0,05 sehingga ada hubungan pengetahuan dengan pemberian ASI. Untuk hubungan sikap dengan pemberian ASI didapatkan hasil p = 0,036 < 0,05 menunjukan bahwa ada hubungan antara sikap dengan pemberian ASI. Saran untuk petugas kesehatan, sebaiknya lebih meningkatkan penyuluhan dan pengenalan tentang manfaat pemberian ASI Eksklusif karena akan sangat membantu memberikan dorongan dan motivasi ibu dalam memberikan ASI pada anaknya. Kata kunci : pengetahuan, sikap, ASI Eksklusif